The last midwife eaudiobook - Dallas, Sandra (Recorded Books Inc., 2015)
With Sandra Dallas's incomparable gift for creating a sense of time and place and characters that capture your heart, The Last Midwife tells the story of family, community, and the secrets that can destroy and unite them. It is 1880 and Gracy Brookens is the only midwife in a small Colorado mining town where she has delivered hundreds, maybe thousands, of babies in her lifetime. The women of Swandyke trust and depend on Gracy, and most couldn't imagine getting through pregnancy and labor without her by their sides. But everything changes when a baby is found dead ... and the evidence points to Gracy as the murderer. She didn't commit the crime, but clearing her name isn't so easy when her innocence is not quite as simple, either. She knows things, and that's dangerous. Invited into her neighbors' homes during their most intimate and vulnerable times, she can't help what she sees and hears. A woman sometimes says things in the birthing bed, when life and death seem suspended within the same moment. Gracy has always tucked those revelations away, even the confessions that have cast shadows on her heart. With her friends taking sides and a trial looming, Gracy must decide whether it's worth risking everything to prove her innocence. And she knows that her years of discretion may simply demand too high a price now ... especially since she's been keeping more than a few dark secrets of her own.